LEWIS BASE ADDUCTS OF LEAD(I1) COMPOUNDS IV*, SYNTHESIS AND CRYSTAL STRUCTURES OF (DINITRATO) (1,4,8,11- TETRA- AZAANDECANE) LEAD(I1) (Journal of Sciences, Islamic Republic of Iran)
The synthesis and single-crystal X-ray structure determination of the title compound (dinitrato) (1,4,8,11 -tetra-azaandecane) lead(II) is described. Crystals are monoclinic, P2 /ca= 10.271 (2)?,b= 13.524(4) ?,c= 11.298(6) ?,?=94.68(3),2=4,R,Rw, 0.036 and 0.041, respectively. The lead atom is eight-coordinate [Pb-N, 2.44 (2) - 2.55 (1)], [Pb-0,2.87 (1) - 3.06 (2)].